Adult Aging Moderates the Relationship Between Trait Cognitive Anxiety and Subjective Everyday Cognitive Difficulties - Spalding, David M.; MacAngus, Kerry; Moen, Martine K.; Nicholls, Louise A. Brown (Frontiers in Psychology, 2021)
The present aim was to determine, across the adult lifespan, the extent to which different dimensions of trait anxiety might affect subjective cognitive difficulties in everyday life. Following Attentional Control Theory (ACT; Eysenck et al., 2007), we predicted that trait anxiety would have a greater effect on attention and verbal abilities than on visual abilities. We also expected trait cognitive anxiety to exhibit more robust relationships with cognition than trait somatic anxiety. Importantly, we predicted that effects of anxiety would be greater in older adults, in line with the Strength and Vulnerability Integration model (SAVI; Charles, 2010). The sample comprised 286 UK-based adults aged 18-93 years. Participants completed self-report measures of trait cognitive and somatic anxiety (the State-Trait Inventory for Cognitive and Somatic Anxiety; STICSA, Ree et al., 2008) and everyday cognitive difficulties (the Multiple Abilities Self-Report Questionnaire; MASQ, Seidenberg et al., 1994). Moderated regression models were constructed, including trait cognitive or somatic anxiety as a predictor of cognitive difficulties, and age as the moderator variable. Covariates included depression, stress (the Depression Anxiety Stress Scales - short form; DASS-21, Lovibond & Lovibond, 1995), gender, current mental health treatment status, and physical health status. When cognitive anxiety was the predictor variable, somatic anxiety was also included as a covariate, and vice-versa. Trait cognitive anxiety and age interacted to predict all MASQ subscales other than visual-perceptual ability. Difficulties with attention, verbal memory, and language abilities were significantly greater at higher levels of anxiety for all age groups, with the effect greatest in older adults. Difficulties with visual-spatial memory were significantly greater at higher levels of anxiety in middle-aged and older adults only. Higher trait somatic anxiety predicted difficulties with verbal memory and language ability independently of age, and interacted with age to predict language difficulties. Interestingly, age also significantly predicted less subjective difficulty with attention, independently of anxiety level. The results show that trait cognitive and somatic anxiety are both related to subjective, everyday cognitive difficulties. However, effects of trait cognitive anxiety are more robust across cognitive domains and tend to increase, or first appear, over the course of the adult lifespan.